Application and Research of Three-Row Pile Retaining Structure in Key Project of Drainage Pumping Station - HU Xubao; YAN Yong (Renmin Zhujiang)
Most of the wing walls at the connection section of forebays in key projects of drainage pumping stations are generally designed as cantilevers,buttresses,or box-type retaining wall structures and are equipped with temporary diversion and supporting measures,which thus require high project investment and long construction period.This paper took the Yaquewei water conservancy project as an example and optimized the scheme of wing walls between the pump station and the sluice at the connection section of the forebay of a large-scale drainage pumping station.After comparison and selection,it was recommended to adopt a three-row pile retaining structure,which is less used in water conservancy projects.The optimized scheme saves the project investment and shortens the construction period.At the same time,three-dimensional finite element numerical simulation technology and other means were used to compare the calculation results with the measured engineering data,so as to demonstrate the technical feasibility of the scheme and summarize the design experience.